The fate of Dinwoody Glacier: present state of mass balance and downstream impacts of glacier runoff - Stamper, Brooke E., author; Bliss, Andrew K., advisor; Grigg, Neil S., committee member; Fassnacht, Steven R., committee member (Colorado State University. Libraries, 2018)
The Wind River Range in Wyoming supports many of the few remaining continental glaciers of the North American Rocky Mountains; the glacier meltwater runoff feeds four major river systems within the U.S. West. Runoff from glaciers affects downstream ecosystems by influencing the quantity, seasonality, and chemistry of the water. We describe the present state of Dinwoody Glacier, the fourth largest glacier in the Wind River Range. We utilize photogrammetry, snow depth measurements, and ablation measurements to characterize surface mass balance for summer of 2017. Localized and nearby stream gauge measurements help to quantify glacial meltwater runoff inputs to Dinwoody Creek. Both of these methods allowed us to put the changes of the Dinwoody Glacier into the broader context of the Missouri River Watershed. If melted, Dinwoody Glacier would no longer provide a reliable source of melt water for thousands of people living in the Missouri River Watershed. Understanding how shrinking glaciers and decreasing melt-water runoff will impact communities and ecosystems downstream is critical for effective environmental management. The response of the Wind River glaciers to future climate is uncertain; however, past research has shown declines in glacial mass, snow cover, snowmelt timing and stream power. The data we collected in the summer of 2017 tells the story of a quickly diminishing and critical resource despite 2017 being a uniquely wet and cold year. While glacier meltwater runoff contributions to Dinwoody Creek were above average, the Accumulation Area Ratio for Dinwoody Glacier in 2017 was 21% suggesting a glacier in severe recession.
Keywords: glacial recession; water resource management; Wind River Range; mass balance; climate change; Wind River Indian Reservation